Immunopathological Dysregulation in Acute Myeloid Leukemia: The Impact of T-bet, RORγt, and FOXP3 on Disease Dynamics - Amira M. Mohamed Mohy El-Din; Buthayna Ahmad AlShaarawy; Eman Zaghloul Kandeel; Dalia Mahmoud AlDewi; Lobna Abdel Azeem Refaat; Borros Arneth; Hussein Sabit (Cells)
The etiology of acute myeloid leukemia (AML) is complex, including genetic and environmental abnormalities. The immune system anomalies play an essential role in the process of leukemogenesis. However, the immunopathological factors, including abnormal T helper (Th) subsets, contributing to the initiation and progression of this neoplasm, require further investigation. Considering the previously mentioned data, we decided to study the expression pattern of transcription factors T-bet, Foxp3, and RORγt that regulate Th1, Treg, and Th17, respectively, in acute myeloid leukemia with correlation to clinical and other investigation data and treatment outcomes. This study was conducted on 80 newly diagnosed patients with AML recruited from the National Cancer Institute, Cairo University, and 25 healthy control subjects. The AML patient cohort consisted of 30 females (37.5%) and 50 males (62.5%), ranging from 18 to 74 years old. The control group was 8 females (32%) and 17 males (68%), with ages ranging from 23 to 40 years old. Samples were provided from the bone marrow of donor cases for allogeneic bone marrow transplantation. The diagnosis of acute myeloid leukemia was based on morphologic and cytochemical evaluation, immunophenotyping, and complementary cytogenetics according to WHO criteria. Upshift from the normal T-bet intensity of power (MFI), RORγt+ CD4+ T lymphocyte frequency (%) with downshift from the normal FOXP3 intensity of power (MFI), may suggest a state of inflammation. In contrast, an upshift from the normal FOXP3+ CD4+ T lymphocyte frequency (%) may reflect a state of immunosuppression in the bone marrow microenvironment of AML. Combined, they constitute a sophisticated scenario of immunological disorder in AML. Co-expression of T-bet and RORγt transcription factors in CD4+ T lymphocytes in both normal and AML groups may suggest CD4+ T lymphocyte plasticity.